ANALISA PERFORMANSI HEAT PUMP MENGGUNAKAN COUNTER FLOW HEAT EXCHANGERS - Kusnandar, Kusnandar; Kusnandar, Kusnandar (P3M Politeknik Negeri Indramayu, 2016)
Heat pump is a device that can be make heat and cool , which is functions as a cooling evaporator can be replaced to be a heating condenser. With adding a heat exchanger in the heat pump can provide better effect of heating and cooling. In this experiment, the heat pump using type hydrocarbon refrigerantand type friendly refrigerant to the environment, one of refrigerant isR-290. From the results that obtained value Coefficient Of Performance (COP) in the heat pump that uses a counter flow heat exchanger is 4.8 while the heat pump that does not use a counterflow heat exchanger obtained COP of 4.1. Efficiencies increase in the heat pump without using counter flow heat exchanger is 74%, otherwise the efficiency decrease of the heat pump using heat pump is 85%.